Narasi Pendidikan Etika Teknologi Berbasis Spiritualitas dalam Sastra Anak Futuristik pada Era Industri 4.0 - Alatas, Mochamad Arifin; Effendy, Moh Hafid; Albaburrahim, Albaburrahim; Romadhon, Sahrul; Rachmayanti, Irma (Islamic Education Management Study Program, Tarbiyah and Teacher Training Faculty, State Islamic University of Madura, 2026)
The development of digital technology and artificial intelligence in the era of Industry 4.0 has brought significant changes to children’s lives, particularly in how they interact, learn, and build moral awareness thereby creating an urgent need for technology ethics education from an early age. Studies on futuristic children’s literature have mostly focused on representations of technology, digital literacy, and future imagination, while the integration of technology ethics and children’s spirituality remains limited. This study aims to examine how futuristic children’s literature represents spirituality-based technology ethics education through narratives that build digital-spiritual ethical awareness and the imagination of future ethics. This research uses a qualitative descriptive approach with narrative analysis of the novel The Wild Robot by Peter Brown. The findings indicate that futuristic children’s literature is able to fosters ethical awareness through relationships, empathy, and self-restraint, and project the imagination of future ethics oriented toward moral responsibility.